Integrative genomics and pathway analysis identified prevalent FA-BRCA pathway alterations in arsenic-associated urinary bladder carcinoma: Chronic arsenic accumulation in cancer tissues hampers the FA-BRCA pathway - Basu, Mukta; Ghosh, Sabnam; Roychowdhury, Anirban; Samadder, Sudip; Das, Pijush; Addya, Sankar; Roy, Anup; Pal, Dilip Kumar; Roychoudhury, Susanta; Ghosh, Amlan; Panda, Chinmay Kumar (Genomics (San Diego, Calif.), 2020)
Arsenic in drinking water is one of the major etiological factors in urinary bladder carcinoma (BlCa). Here, high-resolution CGH-SNP microarray analysis in arsenic accumulated BlCa tissues showed significant (p < 0.05) association of chromosomal alterations with high arsenic (≥112 ng/g) accumulation, further corroborated by high γH2AX nuclear expression. Cytobands 5q11–35, 9p24.3–21.5, 18q11.1–25, etc. showed deletion, whereas 12q was amplified in high arsenic samples (AsH). Consecutively, IPA® found FA-BRCA pathway to be exclusively altered in AsH group. Validation of several key regulatory genes (RAD50, BRIP1, UIMC1, FANCD2, BRCA2 and BRCA1) of the pathway, were performed in independent BlCa cases (n = 81). UIMC1, RAD50 and BRIP1 were differentially deleted and associated with poor survival of AsH samples. Moreover, reduced nuclear expression with diffused cytoplasmic expression of FANCD2 was higher in AsH samples. Collectively, frequent deregulation of RAD50, UIMC1 and BRIP1 may result in reduced nuclear translocation of FANCD2, which may cause more chromosomal aberrations among AsH samples. [Display omitted] •Effective arsenic accumulation in bladder cancer tissues was measured.•Genomic instability was higher in high arsenic samples (AsH; ≥112 ng/g).•Alterations in key regulatory genes of FA-BRCA pathway were higher in the AsH samples.•Low nuclear with diffused cytoplasmic expression of FANCD2 in AsH samples.•Worst prognosis of AsH samples with deletions in RAD50 and UIMC1 was observed.